Transcriptomic insights into the molecular mechanism for response of wild emmer wheat to stripe rust fungus - Ren, Jing; Chen, Liang; Liu, Jian; Zhou, Bailing; Sha, Yujie; Hu, Guodong; Peng, Junhua (Frontiers in Plant Science, 2024)
Introduction Continuous identification and application of novel resistance genes against stripe rust are of great importance for wheat breeding. Wild emmer wheat, Triticum dicoccoides, has adapted to a broad range of environments and is a valuable genetic resource that harbors important beneficial traits, including resistance to stripe rust caused by Puccinia striiformis f. sp. tritici (Pst). However, there has been a lack of systematic exploration of genes against Pst races in wild emmer wheat. Methods Genome-wide transcriptome profiles were conducted on two wild emmer wheat genotypes with different levels of resistance to (Pst (DR3 exhibiting moderate (Pst resistance, and D7 displaying high (Pst resistance). qRT-PCR was performed to verify findings by RNA-seq. Results A higher number of DEGs were identified in the moderately (Pst-resistant genotype, while the highly (Pst-resistant genotype exhibited a greater enrichment of pathways. Nonetheless, there were consistent patterns in the enrichment of pathways between the two genotypes at the same time of inoculation. At 24 hpi, a majority of pathways such as the biosynthesis of secondary metabolites, phenylpropanoid biosynthesis, phenylalanine metabolism, and alpha-Linolenic acid metabolism exhibited significant enrichment in both genotypes. At 72 hpi, the biosynthesis of secondary metabolites and circadian rhythm-plant pathways were notably and consistently enriched in both genotypes. The majority of (WRKY, MADs , and AP2-ERF families were found to be involved in the initial stage of response to Pst invasion (24 hpi), while the MYB, NAC, TCP, and b-ZIP families played a role in defense during the later stage of Pst infection (72 hpi). Discussion In this present study, we identified numerous crucial genes, transcription factors, and pathways associated with the response and regulation of wild emmer wheat to Pst infection. Our findings offer valuable information for understanding the function of crucial Pst-responsive genes, and will deepen the understanding of the complex resistance mechanisms against Pst in wheat.